Sentiments via #Abrahamaccords on the UAE and Israel Normalization - Hafiz Fikrie; Hafid Adim Pradana; Dedik Fitra Suhermanto (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2022)
On 15 September 2020, the UAE normalized relations with Israel, which sparked controversy on Twitter with the #AbrahamAccords. By using Digital Movement Opinion (DMO) and the concept of sentiment analysis, this study aims to determine the sentiment of public opinion that develops on Twitter media related to the normalization of this relationship. This study used a qualitative approach through the use of text mining methods using Natural language Toolkit (NLTK) as a platform in Python to analyze 490 tweets with #AbrahamAccords. The results of the study showed that the sentiment of public opinion that developed on social media Twitter was a positive sentiment with 75% of the 490 tweets. It also showed that views on the relationship between the UAE and Israel on social media Twitter via #AbrahamAccords tend to support this normalization. Some factors that influenced the positive sentiment were the role of the mass media and political actors. Pada 15 September 2020, UEA melakukan normalisasi hubungan dengan Israel yang yang mengundang kontroversi di Twitter dengan #AbrahamAccords. Dengan menggunakan Digital Movement Opinion (DMO) dan konsep sentiment analisis, penelitian ini bertujuan untuk mengetahui sentimen dari opini publik yang berkembang pada media Twitter terkait dengan normalisasi hubungan tersebut. Penelitian ini menggunakan metode kualitatif melalui pemakaian metode teks mining dengan menggunakan Natural language Toolkit (NLTK) sebagai platform di Python guna menganalisis 490 tweets dengan #AbrahamAccords. Hasil penelitian menunjukkan bahwa sentimen dari opini publik yang berkembang di media sosial Twitter adalah sentimen positif dengan 75% dari 490 tweet yang di peroleh. Hal ini menunjukkan bahwa pandangan terhadap hubungan UEA dengan Israel pada media sosial Twitter melalui #AbrahamAccords cenderung mendukung adanya normalisasi tersebut. Beberapa faktor yang mempengaruhi sentiment positif yang terjadi ialah peran media massa dan aktor politik.